Body Fat and Weight Gain in Pregnant Women of Adequate Weight - Oscar Cañizares Luna; Nélida Sarasa Muñoz; Calixto Orozco Muñoz (Revista Finlay)
Assessing the nutritional status of pregnant women, based on the body mass index, is a systematic practice in primary health care institutions in Cuba. Its results have contributed to a significant reduction in maternal and child morbidity and mortality and to the increase in the population's quality of life. However, in pregnant women of adequate weight, pre-gestational nutritional status determined at first consultation, so as those who gain weight during pregnancy, excessive deposits of adipose tissue can be associated in certain body regions and become threats to health present and future of these pregnant women. This situation is not reported in the current anthropometric records from the weight/height ratio according to the body mass index. Hence the convenience of evaluating the body fat of pregnant women of adequate weight, as a more reliable procedure.